Political Economy, Television Industry, and Media Ethics: Case Commodification and structurization in Infotainment Programs in Indonesian Television - Mulharnetti Syas (The Indonesian Journal of Communication Studies, 2010)
Since the last 5 years, television in Indonesia has grown very rapidly. The more television stations, is also increasing production of television shows. Infotainment is one of the television program alternatives. The business side of media should not always be in conflict with ethics. There is constant relationship exists between economic and ethical factors. This research study about the commodification and structuration and associated with media ethics. The formulation of research questions about how the commodification and structuration infotainment programs on Indonesian television industry, and how the media ethics apply to these infotainment programs. In this research will study a causal relationship between structure and agency in the production and consumption of infotainment programs on the television industry in the Indonesia media ethics perspective. This research uses critical paradigm with qualitative methodology. Data collection techniques performed by depth interviews, observation, and analysis of the tape and paperwork. Data analysis using intertextuality. The results show, the television industry is the industry capital-intensive mass media so that more priority to profits than the public interest. A television program aired was not representative of the interests of viewers, including infotainment programs. Commodification of audiences who made the television industry is reflected through the rating. Rating is a tool used to offer the viewers to advertisers. Interplay between structure and agency interests occurs. From the perspective of media ethics, many violations committed by the journalist code of ethics infotainment of the Code of Conduct of Journalism also Broadcasting and Press Standards Program.